2011
DOI: 10.3329/jhpn.v29i4.8446
|View full text |Cite
|
Sign up to set email alerts
|

A Fifteen-year Review of Lymphomas in a Nigerian Tertiary Healthcare Centre

Abstract: In Africa, epidemiological data on the effect of the HIV epidemic on the occurrence of lymphomas are scanty. The 1990s witnessed the alarming rates of HIV/AIDS in Nigeria. The prevalence of HIV/AIDS in Nigeria increased from 1.8% in 1991 to 4.4% in 2005. The aim of this study was to determine whether there have been any changes in the frequency and pattern of lymphomas in view of the HIV/AIDS epidemic in the country. This is a retrospective study of all lymphoma cases diagnosed during 1991-2005. The prevalence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
23
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(29 citation statements)
references
References 27 publications
(29 reference statements)
6
23
0
Order By: Relevance
“…In contrast, a study from Tanzania (Mwakigonja et al , ) suggested an increase in lymphoma prevalence from 1997 to 2001 together with an increase in HIV prevalence. Overall, the most common NHL subtypes in these African studies, regardless of HIV status, are Burkitt or Burkitt‐like lymphoma and DLBCL, with relatively low frequencies of LG B‐NHL (Lazzi et al , ; Parkin et al , ; Mwakigonja et al , ; Bolarinwa et al , ; Mantina et al , ; Oluwasola et al , ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In contrast, a study from Tanzania (Mwakigonja et al , ) suggested an increase in lymphoma prevalence from 1997 to 2001 together with an increase in HIV prevalence. Overall, the most common NHL subtypes in these African studies, regardless of HIV status, are Burkitt or Burkitt‐like lymphoma and DLBCL, with relatively low frequencies of LG B‐NHL (Lazzi et al , ; Parkin et al , ; Mwakigonja et al , ; Bolarinwa et al , ; Mantina et al , ; Oluwasola et al , ).…”
Section: Discussionmentioning
confidence: 99%
“…Several other studies from sub‐Saharan Africa (Table ) have also examined the relative frequencies of lymphoma subtypes (Lazzi et al , ; Parkin et al , ; Mwakigonja et al , ; Bolarinwa et al , ; Oluwasola et al , ), but most of these studies were conducted on a relatively small number of cases with highly variable results, making comparison difficult. In a Nigerian study (Oluwasola et al , ), the prevalence of lymphomas declined in the period from 1991 to 2005 despite an increase in HIV prevalence in the population. In contrast, a study from Tanzania (Mwakigonja et al , ) suggested an increase in lymphoma prevalence from 1997 to 2001 together with an increase in HIV prevalence.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[3][4][5][6]8] The most common subtypes documented were CHL-MC and CHL-NS. [6,8] There are few epidemiological studies of HL in other African countries, with previous studies showing prevalences of HL between 0.5% and 2% of all malignancies, [10,11] 7 -12.5% of all lymphomas [12] and 7 -11% of all lymph node biopsies [13] investigated. HIV seropositivity ranged between 0% and 16%, [10][11][12][13][14] with some studies not testing for HIV owing to lack of availability of the means to do so.…”
Section: Researchmentioning
confidence: 99%
“…[6,8] There are few epidemiological studies of HL in other African countries, with previous studies showing prevalences of HL between 0.5% and 2% of all malignancies, [10,11] 7 -12.5% of all lymphomas [12] and 7 -11% of all lymph node biopsies [13] investigated. HIV seropositivity ranged between 0% and 16%, [10][11][12][13][14] with some studies not testing for HIV owing to lack of availability of the means to do so. [10,11,13] A multi-African study [14] (n=52 cases) and a Nigerian study [11] (n=80) described CHL-MC and CHL-NS as the most common subtypes, whereas studies in Nigeria [13] (n=56) and Malawi [12] (n=31) recorded a predominance of CHL-MC and CHL-LD.…”
Section: Researchmentioning
confidence: 99%